PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK GROUP EXERCISE UNTUK MENGEMBANGKAN SELF EFFICACY SISWA DI SMP PGRI 1 PALEMBANG - Sholehatun Islamiah, Meilda; Syska Purnama Sari; Endang Surtiyoni (IKIP Siliwangi, 2026)
Self efficacy is a self-belief in one's ability to achieve expected goals. Low self-efficacy in students has an impact on student achievement and their inner abilities. The study aims to determine the effect of group guidance with group exercise techniques in developing students' self-efficacy. Group exercise techniques in group guidance which include writing, drawing, and pasting photos as a medium of self-expression are chosen so that students practice self-skills in a supportive group situation. The purposeful sampling technique was used to select 6 students, with 2 students having high self-efficacy, 2 students having moderate self-efficacy, and 2 students having low self-efficacy .This research uses a pre-experimental method with The One Group Pretest Posttest design. Data were collected through a self-efficacy questionnaire developed based on Bandura's theory with aspects of magnitude, generality, and strength. The intervention was carried out for 3 meetings. The results showed a significant increase in self-efficacy scores after receiving group guidance with group exercise techniques with an average pretest score of 126 and an increase in posttest 170 so that the percentage increased to 35% from before and after treatment. The results of the Wilcoxon test show that there is a significant effect with an asymptotic significance value of 0.027 greater than the 0.05 limit, which indicates Ha is accepted and Ho is rejected. This indicates that the group exercise technique applied is effective in developing the self-efficacy of junior high school students.